THE ANALYSIS OF LOW BIRTH WEIGHT INFANTS IN SINGKAWANG CITY - Nasla, U. Evi Nasla (Jurnal Kesehatan Prima, 2018)
Abstract: The efforts of decreasing the infant mortality is focused on the causes of infantâ€™s death. One of them Â is the lowest Birth Weight that can be prevented through a quality and comprehensive antenatal care. The factors that affect the occurrence of low birth weight (LBW) in Singkawang city is age, parity, range of pregnancy, arm circumference, antenatal care, anemia history, newborn weight. The objective study was to determine the factors that affect the occurrence of LBW in Singkawang in 2015. This research employed analytical survey research design with retrospectively approach with cross sectional design. The sample used is the case of newborn with LBW as many as 105 with a ratio of 1: 1 with a total sample of 210 babies. The sample was random sampling. The data analysis used Chi Square and logistic regression test. Chi Square test results showed that there was a significant relationship between age, arm circumference, antenatal care of anemia (p = 0.005, p = 0.013, p = 0.020, p = 0.003) with the incidence of LBW. And there was no significant correlation between parity and range of pregnancy (p = 0.805, p = 0.766). This research is expected to be the basis of evaluating the occurrence of LBW thus it can be detected earlier. Keywords: Age; Parity; Antenatal Care; Arm Circumference; Anemia history; Lowest Birt Weight.